JBendge: An object-oriented system for solving, estimating and selecting nonlinear dynamic models - Viktor Winschel; Markus Krätzig (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
We present an object-oriented software framework allowing to specify, solve, and estimate nonlinear dynamic general equilibrium (DSGE) models. The implemented solution methods for finding the unknown policy function are the standard linearization around the deterministic steady state, and a function iterator using a multivariate global Chebyshev polynomial approximation with the Smolyak operator to overcome the course of dimensionality. The operator is also useful for numerical integration and we use it for the integrals arising in rational expectations and in nonlinear state space filters. The estimation step is done by a parallel Metropolis-Hastings (MH) algorithm using a linear or nonlinear state space filters. Implemented are the Kalman, Extended Kalman, Particle, Smolyak Kalman, Smolyak Sum, and Smolyak Kalman Particle filters. The MH sampling step can be monitored and controlled interactively by sequence and statistics plots. The number of parallel threads can be adjusted to benefit from multiprocessor environments. JBendge is based on the framework JStatCom, which provides a standardized application interface. All tasks are supported by an elaborate multi-threaded graphical user interface (GUI) with project management and data handling facilities.
Keywords: C11; C13; C15; C32; C52; C63; C68; C87; 330; Dynamic stochastic general equilibrium (DSGE) models; Bayesian time series econometrics; Java; software development; Dynamisches Gleichgewicht; CGE-Modelling; Allgemeines Gleichgewicht; Ökonometrisches Modell; Objektorientierte Programmierung; Theorie